Transport properties of a two-dimensional electron gas dressed by light - Pervishko, Anastasiia (2015)
We show theoretically that the strong interaction of a two-dimensional electron gas (2DEG) with a dressing electromagnetic field drastically changes its transport properties. Particularly, the dressing field leads to a giant increase of conductivity (which can reach thousands of percents), resulting in nontrivial oscillating dependence of conductivity on the field intensity, and suppressing the weak localization of 2DEG. As a consequence, the developed theory opens an unexplored way to control transport properties of 2DEG by a strong high-frequency electromagnetic field. From an experimental viewpoint, this theory is applicable directly to quantum wells exposed to a laser-generated electromagnetic wave.